Harmonizing the Legality of Nominee Agreements with Corporate Law in Indonesia - Iin Indriani; Ema Farida (Faculty of Law, Universitas Pekalongan, 2025)
The business process of development that occurs in Indonesia is increasingly marked by the rampant implementation of nominee agreements to form Limited Liability Companies (PT), especially carried out by foreign parties who want to avoid restrictions on share ownership. Although contractually nominee agreements can be categorized as agreements that are appropriate to meet the legal requirements as stipulated in Article 1320 of the Civil Code. However, substantially, its existence is contrary to the principles and provisions of corporate law, especially in Law Number 40 of 2007 concerning Limited Liability Companies. This study aims to analyze the legal disharmony between the legality of agreements according to civil law and the principle of legality of establishment and ownership of shares in company law. This research uses normative juridical methods with laws and regulations, conceptual, and case study approaches. The results of the study show that the nominee agreement creates legal ambiguity that has the potential to harm the legal interests of the parties and weaken the integrity of the national legal system. Therefore, synchronization between the two needs to be done. This synchronization can be done through strengthening supervision, enforcing the principle of transparency, and harmonizing regulations across sectors.